Enrichment of Autotrophic Denitrifiers From Anaerobic Sludge Using Sulfurous Electron Donors - Carboni, M. F.; Florentino, A. P.; Costa, R. B.; Zhan, X.; Lens, P. N. L. (Frontiers in Microbiology, 2021)
This study compared the rates and microbial community development in batch bioassays on autotrophic denitrification using elemental sulfur (S0), pyrite (FeS2), thiosulfate (S2O32–), and sulfide (S2–) as electron donor. The performance of two inocula was compared: digested sludge (DS) from a wastewater treatment plant of a dairy industry and anaerobic granular sludge (GS) from a UASB reactor treating dairy wastewater. All electron donors supported the development of a microbial community with predominance of autotrophic denitrifiers during the enrichments, except for sulfide. For the first time, pyrite revealed to be a suitable substrate for the growth of autotrophic denitrifiers developing a microbial community with predominance of the genera Thiobacillus, Thioprofundum, and Ignavibacterium. Thiosulfate gave the highest denitrification rates removing 10.94 mM NO3– day–1 and 8.98 mM NO3– day–1 by DS and GS, respectively. This was 1.5 and 6 times faster than elemental sulfur and pyrite, respectively. Despite the highest denitrification rates observed in thiosulfate-fed enrichments, an evaluation of the most relevant parameters for a technological application revealed elemental sulfur as the best electron donor for autotrophic denitrification with a total cost of 0.38 € per m3 of wastewater treated.